Identificação de calcificações carotídeas em radiografia panorâmica digital e convencional - Ribeiro, Betania Fachetti (2010)
The frequency of cardiovascular diseases has increased worldwide, and today they are regarded the major cause of mortality and morbidity. Atherosclerosis affects the arteries, with fat deposition in their walls and later calcium salts deposition that may form a calcified atheroma. This study aimed to evaluate the occurrence of calcification in the carotid artery by conventional and digital panoramic radiography in patients aged 40 or older. The study used 728 panoramic radiographs, 600 obtained in direct digital equipment and 128 in film conventional unit. The occurrence of carotid calcification was 7%, and was identified in 51 cases. Patients with calcification in the carotid artery were aged between 43-90 years old, while in women the peak incidence was in the 5th decade of life. In men, the fifth, sixth and eighth decade were the most affected, with no predominance of age. Carotid calcifications were present unilaterally in 30 cases and bilateral in 21 cases. Pearson Chi-square test showed no statistically significant difference in the occurrence of calcification in the carotid artery in male and female, although the percentage was slightly higher among men. Differences in occurrence in conventional and digital panoramic radiographs also showed no statistical difference. The results of this study suggest that panoramic radiography, digital and conventional can be used as an auxiliary method in the identification of carotid calcification.